IMPLEMENTASI GOOD CORPORATE GOVERNANCE PADA KINERJA PERUSAHAAN SEKTOR KEUANGAN DENGAN MANAJEMEN RISIKO SEBAGAI VARIABEL INTERVENING - Ariestya, Putu Yutika; Ardiana, Putu Agus (E-Jurnal Akuntansi, 2016)
The aim of this study was to determine the influence of GCG implementation of the risk management and performance of companies in the financial sector listed on the Indonesia Stock Exchange (BEI). GCG implementation is proxied by the Corporate Governance Perception Index (CGPI). Risk management is proxied by the Non Performing Loan (NPL). Proxied company performance by Return on Equity (ROE). The population in this study amounted to 59 which is the financial sector companies listed on the Stock Exchange and are included in the participant survey by The Indonesian Institute for Corporate Governance (IIGC) in 2009-2013. The sample used was purposive sampling. Data analysis techniques used to examine the relationship between these three variables is the path analysis technique (Path Analysis). The results showed that the effect on risk management GCG, GCG affect the company's performance, and risk management having an effect on the performance of the company. Thus risk management can be an intervening variable between corporate governance and corporate performance.
Keywords: Good Corporate Governance (CGPI), Risk Management (NPL), Corporate Performance (ROE)